Serum carcinoembryonic antigen-related cell adhesion molecule 1 level in postmenopausal women: correlation with β-catenin and bone mineral density - Ma, C.; Shuai, B.; Shen, L.; Yang, Y. P.; Xu, X. J.; Li, C. G. (Osteoporosis international, 2016)
Summary Many epidemiological studies have shown that in some tumors carcinoembryonic antigen-related cell adhesion molecule 1 (CEACAM1) and β-catenin appear to be related. However, it remains to be established whether CEACAM1 is related to β-catenin in osteoporosis. Here, we reveal that CEACAM1 might influence the canonical Wnt/β-catenin pathway to modulate bone metabolism in postmenopausal osteoporosis. Introduction The aim of this study is to assess the serum level of CEACAM1 in postmenopausal women and its correlation with β-catenin and bone mineral density (BMD). Methods The BMD was measured at the lumbar spine (L1–L4) or the femoral neck using dual-energy X-ray absorptiometry (DXA). Serum CEACAM1, β-catenin, receptor activator of nuclear factor kappa-B (RANKL), osteoprotegerin (OPG), β-isomerized C-terminal crosslinking of type I collagen (β-CTX), intact N-terminal propeptide of type I collagen (PINP), estradiol, and insulin were measured in 350 postmenopausal women. Patients were divided according to lumbar spine or femur neck T-scores into osteoporosis (group I), osteopenia (group II), and normal bone mineral density, the latter serving as control. Results Serum CEACAM1 levels were significantly lower in group I and II compared to those in control subjects ( P < 0.001). Serum CEACAM1 levels correlated positively with β-catenin and BMD, but correlated negatively to the ratio between RANKL and OPG. Conclusion This study provides evidence that decreased serum CEACAM1 levels are related to low BMD in postmenopausal women, and that serum CEACAM1 levels correlated positively to β-catenin. It suggests that CEACAM1 might influence the canonical Wnt/β-catenin pathway to modulate bone metabolism.